Innovations, algorithms, and applications in cognitive informatics and natural intelligence - Chui, Kwok Tai 1991-; Lytras, Miltiadis D. 1973-; Liu, Ryan Wen 1987-; Zhao, Mingbo 1982- (Advances in computational intelligence and robotics (ACIR) book series, 2020)
"This book explores innovations, algorithms, and applications in cognitive informatics and natural intelligence"--